Investigating SARS-CoV-2 transmission among co-workers in a University of Northern Italy during COVID-19 pandemic: an observational study - Montecucco, Alfredo; Dini, Guglielmo; Rahmani, Alborz; Kusznir Vitturi, Bruno; Barletta, Chiara; Pellegrini, Luca; Manca, Alessia; Orsi, Andrea; Bruzzone, Bianca; Ricucci, Valentina; De Pace, Vanessa; Guarona, Giulia; et al. (La Medicina del Lavoro, 2021)
Background: This study aimed to investigate SARS-CoV-2 transmission among co-workers at the University of Genoa, Italy, during the second COVID-19 pandemic wave. Methods: A cross-sectional study was carried out in October 2020 – March 2021: RT-PCR confirmed cases of COVID-19 notified to the Occupational Health Service were included in the analysis. Results: Among the n = 201 notified cases, contact tracing of n = 53 individuals identified n = 346 close contacts. The household setting (IRR = 36.8; 95% CI: 4.9-276.8; p < 0.001) and sharing eating areas (IRR = 19.5; 95% CI: 2.5-153.9; p = 0.005) showed the highest Secondary Attack Rates (SARs) compared to the office setting. Fatigue (IRR= 17.1; 95% CI: 5.2-55.8; p < 0.001), gastrointestinal symptoms (IRR= 6.6; 95% CI: 2.9-15.2; p< 0.001) and cough (IRR= 8.2; 95% CI: 3.7-18.2; p= p< 0.001) were associated with transmission of infection. Polysymptomatic cases (IRR= 23.1; 95% CI: 3.1-169.2; p = 0.02) were more likely to transmit the infection. Among COVID-19 index cases aged >60 years (OR = 7.7; 95% CI: 1.9-31.9; p = 0.0046) SARs were higher than in other age groups. Wearing respiratory protections by both the case and the close contact resulted an effective measure compared with no use (IRR = 0.08; 95% CI: 0.03-0.2; p = < 0.0001). Conclusions: Accurate infection monitoring and contact tracing was useful to identify the main situations Conclusions: Accurate infection monitoring and contact tracing was useful to identify the main situations of SARS-CoV-2 transmission in the workplace, and hence for risk assessment and prevention programs.